Facile Synthesis of Triazoles using Electrospray‐Deposited Copper Nanomaterials to Catalyze Azide‐Alkyne Cycloaddition (AAC) Click Reactions. Issue 10 (5th October 2022) - Ghosh, Jyotirmoy; Cooks, R. Graham
Abstract: Electrospray deposition of copper salt‐containing microdroplets onto the liquid surface of an electrically grounded reaction mixture leads to the formation of Cu nanoclusters, which then catalyze the azide‐alkyne cycloaddition (AAC) reaction to form triazoles. This method of in situ nanocatalyst preparation provided 17 times higher catalytic activity compared to that in the conventional catalytic reaction. The gentle landing of the Cu‐containing droplets onto the liquid surface forms a thin film of catalyst which promotes the heterogeneous AAC reaction while showing diffusion‐controlled kinetics. UV‐vis spectral characterization confirms that the catalyst is comprised of Cu nanoclusters. This unique catalytic strategy was validated using several substrates and the corresponding products were confirmed by tandem mass spectrometry (MS/MS) analysis. Abstract : A heterogeneous thin film of Cu nanocatalyst, formed by electrospray deposition of microdroplets containing copper salts directly onto the liquid surface of the reaction solution, drives the synthesis of triazoles by the azide‐alkyne cycloaddition (AAC) click reaction an order of magnitude faster than does the conventional catalyst.Facile Synthesis of Triazoles using Electrospray‐Deposited Copper Nanomaterials to Catalyze Azide‐Alkyne Cycloaddition (AAC) Click Reactions (J. Ghosh and R. G. Cooks) @AstonlabsPurdue